Alex Cross, Run - Patterson, James (Alex Cross series;, 2013)
In the aftermath of a disgraced plastic surgeon's release from prison, Detective Alex Cross investigates the murder of a young mother whose newborn has disappeared, a case that is further complicated by two additional killings